Psychological care of women with a family history of breast cancer - Hopwood, Penelope (Psicooncología, 2005)
In parallel to the development of clinical cancer genetics services for women with a significant history of breast cancer, there has been a growing need to identify the psychological sequelae to risk ascertainment, predictive genetic testing and preventive breast surgery. The organisation and structure of cancer genetics clinics vary widely both nationally and across Europe, as does the level of integration of psychological care: available research shows little variation in psychosocial outcomes but cultural factors affect attitudes to and uptake of predictive testing and preventive surgery. There is general agreement that risk counselling can be beneficial without inducing or increasing psychological morbidity. Health professionals in cancer genetic counselling, testing and risk management services increasingly use clinical protocols and professional guidelines.Routine psychological support is not required for the majority of women with a family history of breast cancer, but access to psychological services should be in place for women with high distress relating to the family history or those undergoing predictive testing or preventive surgery. Genetics staff should be aware of potential adverse psychological consequences of risk assessment and risk management interventions, and be adequately trained to elicit women´s concerns and involve psychosocial colleagues where appropriate.